Sidney Sheldon's After the darkness - Bagshawe, Tilly (William Morrow, 2010)
Blessed with the face of an angel and the guileless, trusting nature of a child, Grace Brookstein is the prized wife of the king of Wall Street, Lenny Brookstein. Despite the stock market's terrifying collapse, the Brooksteins' glamorous lifestyle of polo tournaments and jets remains untouched--until the day Lenny goes sailing from their Nantucket beach estate and never comes home. When his abandoned yacht is found far out at sea, Grace is devastated. She has no idea that his disappearance is just the beginning of a dark, terrifying nightmare of murder, lies, greed, and betrayal that will shatter her life and destroy everything she has ever known.